A simulation function approach for optimization by approximate solutions with an application to fractional differential equation - Lo'lo', Parvaneh; Shams, Maryam; Radenović, Stojan (Nonlinear Analysis: Modelling and Control, 2024)
In this work, we study the existence and uniqueness of a common best proximity point for a pair of nonself functions that are not necessarily continuous using the simulation function. In the following, we state important common best proximity point theorems as results of the main theorems of this article. This achievement allows us to have an example that covers our main theorem but does not apply to the Banach contraction principle. Finally, an application of a nonlinear fractional differential equation to support the obtained conclusions.
Keywords: simulation functions; common best proximity point; (Zd; T)-contraction; P-property; commute proximally; fractional differential equation